TECEPEBI SIMULASI DAN CHATBOT DALAM PENGAJARAN BAHASA INGGRIS STUDI KASUS: UPT SD NEGERI 060941 - Manullang, Evi Yanti; Nissa, Fachrun; Simanjuntak, Mutiara S.; Iskandar, Iskandar; Riduan, Suwardy (Smart Education, 2025)
Abstract: English learning at the elementary school level is still limited, especially in developing authentic speaking skills. This research developed TeCePeBi (Intelligent Technology for Speaking Learning), a chatbot-based interactive media + simulation that applies a communicative approach. Using the ADDIE R&D model, the system was designed, built, and tested on students of SD Negeri 060889, Medan (n = 45). The initial phase of the trial (1020 students) resulted in a prototype that was then tested on a larger group (30 students) for 8 weeks. Evaluations include a pre/posttest of speaking skills, a confidence questionnaire, and a satisfaction interview. The results showed a significant increase in speaking scores (Δ = + 18.2 points, p < 0.01) as well as an improvement in the perception of self-confidence (the average score increased from 3.1 to 4.3 on a scale of 5). In addition, 87% of students reported a more independent and flexible learning experience. These findings confirm the potential of TeCePeBi as an AI-based solution to improve English spoken competence in elementary school students. Keyword: tecepebi; primary school; speaking skills; chatbot; Simulation Abstrak: Pembelajaran bahasa Inggris pada tingkat Sekolah Dasar (SD) masih mengalami keterbatasan, terutama dalam mengembangkan keterampilan berbicara yang autentik. Penelitian ini mengembangkan TeCePeBi (Teknologi Cerdas untuk Pembelajaran Berbicara), sebuah media interaktif berbasis chatbot + simulasi yang menerapkan pendekatan komunikatif. Menggunakan model R&D ADDIE, sistem dirancang, dibangun, dan diuji pada siswa SD Negeri 060889, Medan (n = 45). Uji coba tahap awal (10‑20 siswa) menghasilkan prototipe yang kemudian diuji pada kelompok lebih besar (30 siswa) selama 8 minggu. Evaluasi meliputi pre‑/post‑test keterampilan berbicara, kuesioner kepercayaan diri, dan wawancara kepuasan. Hasil menunjukkan peningkatan signifikan skor berbicara (Δ = + 18,2 poin, p < 0,01) serta peningkatan persepsi kepercayaan diri (skor rata‑rata naik dari 3,1 menjadi 4,3 pada skala 5). Selain itu, 87 % siswa melaporkan pengalaman belajar yang lebih mandiri dan fleksibel. Temuan ini menegaskan potensi TeCePeBi sebagai solusi berbasis AI untuk memperbaiki kompetensi lisan bahasa Inggris pada siswa SD. Kata kunci: tecepebi; sekolah dasar; keterampilan berbicara; chatbot; simulasi